Clinical outcome of SARS-CoV-2 infections occurring in multiple myeloma patients after vaccination and prophylaxis with tixagevimab/cilgavimab - Duminuco, Andrea; Romano, Alessandra; Leotta, Dario; La Spina, Enrico; Cambria, Daniela; Bulla, Anna; Del Fabro, Vittorio; Tibullo, Daniele; Giallongo, Cesarina; Palumbo, Giuseppe A.; Conticello, Concetta; Di Raimondo, Francesco (Frontiers in Oncology, 2023)
Introduction Patients with multiple myeloma (MM) frequently reported immune impairment with an increased risk for infection-related mortality. We aimed to evaluate the immune response in MM patients vaccinated for SARS-CoV-2 during active treatment. Methods We enrolled 158 patients affected by active MM or smoldering MM (SMM) and 40 healthy subjects. All subjects received 2 or 3 doses of the BNT162b2 (Pfizer/BioNTech) vaccine, and the anti-spike IgG values were evaluated after every dose. We applied the Propensity Score Matching (PSM) as a consequence of the limited sample size and its heterogeneity to adjust for differences in baseline clinical variables between MM patients who achieved or not a vaccine response after 2 or 3 doses. Results At 30 days from the second dose, the median antibodies level in MM was 25.2 AU/mL, lower than in SMM and in the control group. The same results were confirmed after the third dose, with lower median anti-spike IgG levels in MM, compared to SMM and control group. Following PSM, lack of response to SARS-CoV-2 complete vaccination plus boost was associated with age more than 70 years old and use of high-dose of steroids. We failed to identify an association between specific treatment types and reduced vaccine response. The use of prophylaxis with tixagevimab/cilgavimab for 40 non-responder patients after 3 doses of vaccine has proven to be an effective and safe approach in reducing the risk of serious illness in the event of a breakthrough SARS-CoV-2 infection, faced with a mild symptomatic course, and in providing protection instead of long-term humoral immune vaccine responses. Following PSM, only the high-risk cytogenetic abnormalities were associated with an increased risk of developing a breakthrough SARS-CoV-2 infection. Conclusion Monitoring the immune response is fundamental in MM patients that remain highly vulnerable to SARS-CoV-2 despite the vaccine. The use of prophylaxis with tixagevimab/cilgavimab can guarantee better protection from the severe form of the disease.